Principles of electric circuits - Floyd, Thomas L. (Prentice Hall, 1997)
A text/CD-ROM introducing basic electrical concepts and circuits, featuring chapter section reviews, worked examples, summaries, glossaries, key formulas, self-tests, problems, and selected answers. This fifth edition contains new PSpice sections in all chapters, a full-color format, and related exe